STATUS CEMARAN DAN UPAYA PENGENDALIAN AFLATOKSIN PADA KOMODITAS SEREALIA DAN ANEKA KACANG - Wisnu Broto (Badan Penelitian dan Pengembangan Pertanian, 2018)
Cereals and nuts commodities play a major role in present and future human consumption patterns. Increased production of these commodities that have been achieved will not mean when both are not safe for consumption. Aflatoxin contamination is one of the food safety indicators that determine consumer acceptance. The high prevalence of aflatoxicosis in South and Southeast Asia are 81% and 54% respectively implies high aflatoxin contamination of cereals and nuts consumed in the area. Aflatoxin contamination in Indonesia, especially in corn and peanut is detected more than 20 ppb, so it needs attention for the handling and controlling. The technology for reducing or eliminating aflatoxin contamination in food products up to 97% has been generated from many studies. The application of such technology is commercially constrained by aspects of the procedural complexity and limitations of industrial support devices from upstream to downstream. Aflatoxin contamination in addition to adversely affecting health also causes economic losses of the commodities concerned, but the regulatory limitations vary greatly. Indonesia sets the maximum limit of aflatoxin on cereals and nuts relatively higher (20 35 ppb) than any other country in the world, so it needs to be re-examined through multidisciplinary research and conprehensive studies to be scientifically tested with economic and political considerations to deal with the increasingly competitive competition in the global market.Keywords: Cereals, various nuts, aflatoxin, food safety AbstrakKomoditas serealia dan aneka kacang memegang peran penting dalam konsumsi pangan pada saat ini dan ke depan. Peningkatan produksi komoditas tersebut tidak berarti manakala tidak aman dikonsumsi. Cemaran aflatoksin merupakan salah satu indikator keamanan pangan yang menentukan penerimaan konsumen. Prevalensi aflatoksikosis yang tinggi di Asia Selatan (81%) dan Asia Tenggara (54%) menyiratkan masih tingginya cemaran aflatoksin pada produk serealia dan aneka kacang yang dikonsumsi. Cemaran aflatoksin di Indonesia, khususnya pada jagung dan kacang tanah, terdeteksi lebih dari 20 ppb, sehingga perlu penanggulangan serius. Teknologi pengurangan atau penghilangan cemaran aflatoksin hingga 97% pada produk pangan telah banyak dihasilkan dari berbagai penelitian. Penerapan teknologi tersebut secara komersial terkendala dari aspek kerumitan prosedural dan keterbatasan perangkat pendukung industrial dari hulu hingga hilir. Cemaran aflatoksin selain berdampak negatif pada kesehatan juga menyebabkan kerugian ekonomi, namun pengaturan batasannya sangat beragam. Indonesia menetapkan batas maksimum aflatoksin pada serealia dan aneka kacang relatif tinggi (2035 ppb) daripada negara lain, sehingga perlu dicermati kembali melalui penelitian komprehensif multidisiplin agar lebih teruji secara ilmiah dengan pertimbangan ekonomis dan politis untuk menghadapi persaingan yang semakin ketat di pasar global.Kata kunci: Serealia, aneka kacang, aflatoksin, keamanan pangan.